Pemodelan Awal Ground Penetrating Radar dengan Metode Discontinuous Galerkin dan PML Berenger - Pranowo (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2016)
This paper discusses the development of Discontinuous Galerkin method, which has both linear shape function and weight function, for modeling Ground Penetrating Radar (GPR) in heterogeneous media. The triangular meshes are used due to their flexibility to deal with complex geometries. The Berenger Perfectly Matched Layer (PML) is used as absorbing boundary condition at the truncation boundaries. The numerical results of the DG method are compared with the exact solutions and the numerical results of FDTD method and the comparisons show that DG method has better accuracy than FDTD method and more stable for long time simulation. The simulation results of GPR show that the PML works well. Propagating waves at the edge of absorbing boundaries can be suppressed without any significant reflection. The results also show that various waves e.g., transmission waves, reflection waves, and diffraction waves produced by heterogeneous material can be simulated well.